1999
DOI: 10.1016/s0896-6273(00)80783-7
|View full text |Cite
|
Sign up to set email alerts
|

Laser Ablations Reveal Functional Relationships of Segmental Hindbrain Neurons in Zebrafish

Abstract: Segmentation of the vertebrate brain is most obvious in the hindbrain, where successive segments contain repeated neuronal types. One such set of three repeated reticulospinal neurons--the Mauthner cell, MiD2cm, and MiD3cm--is thought to produce different forms of the escape response that fish use to avoid predators. We used laser ablations in larval zebrafish to test the hypothesis that these segmental hindbrain cells form a functional group. Killing all three cells eliminated short-latency, high-performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
418
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 380 publications
(442 citation statements)
references
References 27 publications
23
418
1
Order By: Relevance
“…The discrete organization that we see, which differs from previously observed distributed activity 4,18,30 , is made apparent by the ability to evoke simple motor patterns with controlled visual stimulation. The fact that more complex behaviors are associated with distributed activation of many neurons is consistent with a model in which subsets of neurons initiate distinct components of the behavior 31,32 .Additional evidence for a distributed motor command has come from a number of studies that found that ablations do not abolish specific behaviors, although they can alter their latency and kinematics 16,17,[33][34][35] . Here, an ablation guided by an observed functional organization was able to completely abolish a specific behavior; optomotor turns in one direction were specifically eliminated by ablation of the small number of cells responsive to turn-evoking stimuli.…”
mentioning
confidence: 53%
See 3 more Smart Citations
“…The discrete organization that we see, which differs from previously observed distributed activity 4,18,30 , is made apparent by the ability to evoke simple motor patterns with controlled visual stimulation. The fact that more complex behaviors are associated with distributed activation of many neurons is consistent with a model in which subsets of neurons initiate distinct components of the behavior 31,32 .Additional evidence for a distributed motor command has come from a number of studies that found that ablations do not abolish specific behaviors, although they can alter their latency and kinematics 16,17,[33][34][35] . Here, an ablation guided by an observed functional organization was able to completely abolish a specific behavior; optomotor turns in one direction were specifically eliminated by ablation of the small number of cells responsive to turn-evoking stimuli.…”
mentioning
confidence: 53%
“…Additional evidence for a distributed motor command has come from a number of studies that found that ablations do not abolish specific behaviors, although they can alter their latency and kinematics 16,17,[33][34][35] . Here, an ablation guided by an observed functional organization was able to completely abolish a specific behavior; optomotor turns in one direction were specifically eliminated by ablation of the small number of cells responsive to turn-evoking stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Laser ablation has been applied to study locomotor networks. In zebrafish cyan (488-nm) laser exposure for 10-12 min photoablated reticulospinal neurons by augmenting the toxicity of indicator dyes, revealing specific roles for Mauthner cells and their homologs in short-latency escape behaviors (19). UV lasers (≈400 nm) were used in Caenorbabditis elegans to investigate locomotion, chemotaxis, and mechanosensation (20).…”
Section: Discussionmentioning
confidence: 99%